2019
DOI: 10.1038/s41598-019-40178-5
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an observational assessment tool for multifaceted evaluation of faecal condition

Abstract: Faecal volume, form, colour, and odour are associated with various diseases, dietary habits, and the gut microbiome. Multifaceted assessment of faecal condition will be needed for future research and practice. Faecal observation has advantages, as it is non-invasive, frequent, and easy. We have developed and validated an illustrative card tool for comprehensively faecal assessment. In 38 healthy adults, observations of volume, form, colour, and odour of faeces using the tool were compared to the objective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
(57 reference statements)
0
14
0
1
Order By: Relevance
“…The strength of this study is in nding a veri ed association between stool patterns and plasma and fecal fatty acids. The multifaceted, self-reported questionnaires used to assess the stool status had previously been validated against objective fecal characteristics as well [41]. In addition, we showed that twice self-reported stool status was highly reproducible and believe that it is unlikely for there to have been misclassi cation when done in this manner.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The strength of this study is in nding a veri ed association between stool patterns and plasma and fecal fatty acids. The multifaceted, self-reported questionnaires used to assess the stool status had previously been validated against objective fecal characteristics as well [41]. In addition, we showed that twice self-reported stool status was highly reproducible and believe that it is unlikely for there to have been misclassi cation when done in this manner.…”
Section: Discussionmentioning
confidence: 75%
“…Stool status was assessed using the multifaced self-reported questionnaire called the "intestinal visible sheet", which covers the 5-stool status variables (frequency, volume, color, shape, and odor) and was previously developed and validated against objective measurements of fecal characteristics including fecal weight, moisture, hardness, and color in adults [41]. In the NEXIS cohort study, all participants were given similar stool questionnaires assessing both "habitual stool status" and "stool status when collecting fecal samples (excluding stool frequency)" at the same time.…”
Section: Evaluation Of Stool Statusmentioning
confidence: 99%
“…The strength of this study is in finding a verified association between stool patterns and plasma and fecal fatty acids. The multifaceted, self-reported questionnaires used for stool status assessment had previously been validated against objective fecal characteristics as well [ 42 ]. In addition, we showed that twice self-reported stool status was highly reproducible and believe that it is unlikely for there to have been misclassification when done in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…Stool status was assessed using the multifaced self-reported questionnaire called the “intestinal visible sheet”, which covers the 5-stool status variables (frequency, volume, color, shape, and odor) and was previously developed and validated against objective measurements of fecal characteristics including fecal weight, moisture, hardness, and color in adults [ 42 ]. In the NEXIS cohort study, all participants were given similar stool questionnaires assessing both “habitual stool status” and “stool status when collecting fecal samples (excluding stool frequency)” at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…All participants answered a questionnaire on anthropometric data, medical history, fecal characteristics, dietary habits, physical activity, and sleep; a total of 76 items common to two cohorts were extracted as variables (Table S1). Fecal volume, form and color were evaluated by using our assessment card tool for NIBIOHN cohort as described previously [35] with slight modi cations related to volume and color for MORINAGA cohort. To assess daily dietary intake, we asked subjects to answer a different questionnaire, the Brief Self-Administered Diet History Questionnaire (BDHQ), to estimate the intake volume of 58 food and beverage items consumed in the preceding month [36] (Table S1).…”
Section: Questionnaire About Covariatesmentioning
confidence: 99%